2001
DOI: 10.1143/jjap.40.5419
|View full text |Cite
|
Sign up to set email alerts
|

Inductively Coupled Plasma Source with Internal Straight Antenna

Abstract: An inductively coupled plasma source with an internal straight antenna was developed. By inserting an antenna into plasma, the induction of a strong electric field in the plasma and the efficient transmissions of power to plasma is enabled. However, there was a practical problem in that antenna sputtering occurred. Suppression of antenna sputtering and methods of insulating the antenna were studied. Consequently, it was found that sputtering impurities were reduced by covering the straight antenna with a quart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…[1][2][3] As the number of transistors in a single chip is increasing by a factor of ∼ 2 in a year and therefore device size is continuously shrinking, that results in increasing fabrication cost. To optimize the fabrication cost, it is necessary to do plasma processing at large area wafer.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] As the number of transistors in a single chip is increasing by a factor of ∼ 2 in a year and therefore device size is continuously shrinking, that results in increasing fabrication cost. To optimize the fabrication cost, it is necessary to do plasma processing at large area wafer.…”
Section: Introductionmentioning
confidence: 99%
“…For manufacturing solar panels using a plasma-enhanced chemical vapor deposition (PE-CVD) process, a higher plasma density and a larger yet uniform plasma zone are thus advantageous. Many methods have been proposed to generate such high-density plasmas [5][6][7], and recently, an inductively coupled plasma (ICP) system using arrays of internal low inductance antennas (LIA) has been proposed to produce large-area, highly crystallized ncSi:H films [8][9][10]. The LIA units can produce high-density plasma with low plasma potential (as low as 10 V, thus low plasma damage to the deposited film) by decreasing the electrostatic coupling within the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods so far have been proposed to generate plasma containing high-density radicals [1][2][3]. Recently, it was reported that highly crystallized nc-Si films with good interface quality could be deposited by certain inductively coupled plasma chemical vapor deposition (ICP-CVD) system equipped with internal low-inductance-antennas (LIA) [4].…”
Section: Introductionmentioning
confidence: 99%